New Progress in Azole Compounds as Antimicrobial Agents - Zhang, Hui-Zhen; Gan, Lin-Ling; Wang, Hui; Zhou, Cheng-He (Mini Reviews in Medicinal Chemistry, 2017)
The increasing incidence of microbial resistance and newly emerging pathogens have become a serious challenge for public health. More and more efforts have been directed to the development of new antimicrobial agents with distinct mechanisms from the well-known classes of clinical drugs. The extensive clinical utilization of azole-based medicinal drugs has evoked numerous attentions, and their researches and developments have been a quite rapid developing and active highlight topic with an infinite space. Consideration of our researches on azole compounds and other literature in recent three years, this review scientifically reviewed the new progress of azole derivatives as antibacterial, antifungal, antitubercular and antiviral agents, including mono-nitrogen azoles (oxazoles, thiazoles and carbazoles), bis-nitrogen azoles (imidazoles, pyrazoles and benzimidazoles) and tri-nitrogen azoles (triazoles and benzotriazoles) as well as tetrazole derivatives. It was hoped that this review would be helpful for the design and development of highly efficient azole derivatives with high bioactivity and low toxicity.
Keywords: imidazole